2019
DOI: 10.1038/s41396-019-0360-9
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids as wetting agents: surface translocation by Porphyromonas gingivalis

Abstract: Our understanding of how oral microbiota adapt in response to changes in their surroundings remains limited. This is particularly true of the slow-growing anaerobes that persist below the gum line. Here, we report that the oral anaerobe Porphyromonas gingivalis strain 381 can surface translocate when sandwiched between two surfaces. We show that during movement, this bacterium alters its metabolism, specifically side products of arginine utilization including citrulline and ornithine accumulated in the translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 92 publications
5
58
0
Order By: Relevance
“…gingivalis strain W83 was used in this study along with the matching SPT mutant (W83 ΔPG1780), which was generated and characterized previously (Moye et al 2016). RNA was extracted from cells grown anaerobically in TSBHK to an O.D.600 of 1.0, the quality was then assessed and sequencing was performed and analyzed as previously described (Moradali et al 2019;Moye et al 2019).…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…gingivalis strain W83 was used in this study along with the matching SPT mutant (W83 ΔPG1780), which was generated and characterized previously (Moye et al 2016). RNA was extracted from cells grown anaerobically in TSBHK to an O.D.600 of 1.0, the quality was then assessed and sequencing was performed and analyzed as previously described (Moradali et al 2019;Moye et al 2019).…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…A type IX secretion system is involved in pathogenesis and also is required for modification of the environment, enabling P. gingivalis to surface translocate between surfaces in a sandwich model. Metabolomic studies revealed genetic and metabolic adaptation of migrating populations through multiple pathways, including folate biosynthesis and electron transport systems (79).…”
mentioning
confidence: 99%
“…This novel secretion system plays a role in gliding motility, 50 and secretion of virulence factors, 51 and as we recently reported, it is central to P. gingivalis surface translocation. 52 In P. gingivalis, T9SS transports select proteins across the outer membrane that are involved in virulence, e.g., gingipains RgpA, RgpB, and Kgp. 9,51 As shown in Table 1, RNA-seq analysis revealed that an extracytoplasmic function (ECF) sigma factor (PGN_0274) was significantly upregulated in the ΔrelΔrshB mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Sample quality determination and sequencing were performed by gene expression and genotyping core in the ICBR. 52 The program 'Rockhopper' 64 was used for aligning sequencing reads to the genome reference of P. gingivalis 381. We eliminated any of the sequencing reads with a q value > 0.05 and a fold change of <1.5.…”
Section: G Mellonella Model Of Systemic Infectionmentioning
confidence: 99%